2021
DOI: 10.3389/fmicb.2021.692423
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SARS CoV Envelope Protein by Flavonoids and Classical Viroporin Inhibitors

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV), an enveloped single-stranded positive-sense RNA virus, is a member of the genus Betacoronavirus, family Coronaviridae. The SARS-CoV envelope protein E is a small (∼8.4 kDa) channel-forming membrane protein whose sequence is highly conserved between SARS-CoV and SARS-CoV-2. As a viroporin, it is involved in various aspects of the virus life cycle including assembly, budding, envelope formation, virus release, and inflammasome activation. Here, SARS-CoV E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 61 publications
1
38
1
Order By: Relevance
“…We observed a similar response from two-electrode voltage clamp recordings in Xenopus laevis oocytes microinjected with E-protein cRNA (data not shown). Recent studies, on the other hand, have reported a pH-dependent current-voltage relationship where outward currents are elicited in acidic buffer conditions (Breitinger et al, 2021; Cabrera-Garcia et al, 2021). Given the lack of current response to mono- or divalent cations, we investigated the channel’s sensitivity and/or permeability to protons by decreasing the pH of our standard extracellular buffer and measuring the current in response to a voltage ramp.…”
Section: Resultsmentioning
confidence: 99%
“…We observed a similar response from two-electrode voltage clamp recordings in Xenopus laevis oocytes microinjected with E-protein cRNA (data not shown). Recent studies, on the other hand, have reported a pH-dependent current-voltage relationship where outward currents are elicited in acidic buffer conditions (Breitinger et al, 2021; Cabrera-Garcia et al, 2021). Given the lack of current response to mono- or divalent cations, we investigated the channel’s sensitivity and/or permeability to protons by decreasing the pH of our standard extracellular buffer and measuring the current in response to a voltage ramp.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of cellular ion homeostasis has been proven to promote NLRP3 inflammasome activation and cell pyroptosis during SARS-CoV-2 infection, thus ion-channel inhibitors (such as Amantadine, Memantine, 195 Rimantadine, 196 Tretinoin 197 ) could be utilized in treatment with COVID-19 patients. Amantadine displayed antiviral activity via directly blocking the ion channel encoded by SARS-CoV-2 E protein in vitro.…”
Section: Pyroptosis and Sars-cov-2mentioning
confidence: 99%
“…Another study demonstrated that protein E might also be a promising target for anti-COVID drugs. It was shown that some flavonoids, in particular epigallocatechin and quercetin, as well as rimantadine and 5-( N , N -hexamethylene)amiloride (HMA), may serve as inhibitors of the protein E channel [ 125 ] (Fig. 1 A).…”
Section: Drugs Inhibiting Assembly and Release Of The Virus Targeting...mentioning
confidence: 99%